PENGARUH PEMBERIAN LIMBAH BAGLOG JAMUR TIRAM PADA PERTUMBUHAN DAN HASIL TANAMAN CAISIM (Brassica juncea L.) - Esna Dilli Novianto; Nurul Anindyawati; Nindya Nur Aina Kasih (Biology Department, Mathematics and natural science, Tadulako University, 2023)
Caisim (Brassica juncea L.) is one of the most popular vegetable crops in the community. However, the production of caisim is not commensurate with the amount of consumer demand. Currently, one of the efforts made by farmers is to increase caisim production by adding inorganic fertilizers. This method can leave residues so that other alternatives are needed, such as the use of organic fertilizers that are more environmentally friendly. One of the potential sources of organic matter is oyster mushroom baglog waste because it contains a number of nutrients that can act as soil improvement materials. This study aims to study the effect of adding oyster mushroom baglog waste to the growth and yield of caisim (Brassica juncea L.) plants. This study used a factorial Completely Randomized Block Design with 4 treatments and 5 blocks. The treatments consisted of 0 g, 300 g, 600 g and 900 g of baglog oyster mushroom waste. The data obtained were analyzed for variance and continued with the orthogonal polynomial test. The results showed that the control treatment was better than the other treatments. It is suspected that the oyster mushroom baglog waste did not undergo a good fermentation process so that the content of C-organic, N, P and K was low which resulted in fewer nutrients being available for plants. Oyster mushroom baglog waste is not recommended for caisim cultivation practices.